(untitled) (Management and Connections Journal, 2021)
This article aimed to objective a bibliometric analysis of the national production of articles on work engagement, in the period between 2010 and 2019, having as reference papers indexed based on journals of the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES) and the electronic platform of the Scientific Periodicals Electronic Library (SPELL). 74 articles were identified, among which 15 were effectively analyzed, since their content deals with engagement as an element of organizational behavior. It is concluded that, the discussion on the subject is still incipient, its dissemination takes on journals on administration, management and psychology, there is no significant concentration of publications in relation to the question of authorship, the construct has been problematized individually or in association with other behavioral themes, research has been based predominantly on three-dimensional diagnostic instruments and the contributions of studies reflect phenomena and organizational processes.